Survival and degradation of Salmonella enterica serotype Enteritidis in intestinal epithelial cells in vitro - Saarinen, Marja; Pelliniemi, L. J.; Granfors, Kaisa (Journal of Medical Microbiology, 1996)
The survival and fate of Salmonella enterica serotype Enteritidis in Henle-407 human intestinal epithelial cells was investigated during prolonged incubation to evaluate the persistence of causative microbes and the relationship to patients developing reactive arthritis. Most of the bacteria were killed and degraded quite soon after infection of the cells, but there were still live bacteria inside the cells for up to 14 days. These results suggest that in patients developing reactive arthritis the salmonellae could persist in the epithelial cells and spread within the host to the joint and be present there at the time of the inflammatory response. Production of marked amounts of nitric oxide was observed as a novel response to salmonella infection in human intestinal epithelial cells. The present experimental procedure appears to be a suitable model to further investigate host-bacteria interaction in HLA-B27 positive cells from patients developing reactive arthritis.